Planning, Connecting, and Financing Cities--Now : Priorities for City Leaders - World Bank (Washington, DC: World Bank, 2013)
This report provides Mayors and other policymakers with a policy framework and diagnostic tools to anticipate and implement strategies that can avoid their cities from locking into irreversible physical and social structures. At the core of the policy framework are the three main dimensions of urban development. · Planning— where the focus is on making land transactions easier, and making land use regulations more responsive to emerging needs especially to coordinate land use planning with infrastructure, natural resource management, and risks from hazards; · Connecting—where the focus is on making a city’s markets (for labor, goods, and services) more accessible to neighborhoods in the city and to other cities. Here the focus is also on investing in public transport, and pricing private transport fully; and · Financing— where the focus is on how a city can leverage its own assets to finance new assets for example, through land value capture, establishing creditworthiness for local governments and utilities to access domestic debt and bond markets and how to set clear and consistent rules to attract private investors to create jobs in cities. This report also distills lessons from prototypes urbanization diagnostics which have been piloted to reflect challenges for countries at nascent (Uganda, Vietnam), intermediate (China, India, Indonesia), and mature (Brazil, Colombia, South Korea, Turkey) urbanization. These diagnostics under the World Bank's Urbanization Review program have engaged strategic counterparts, such as those in national ministries of finance and planning, in thinking about policy choices that influence urbanization and city development.